Evaluating copper isotope fractionation in the metallurgical operational chain: An experimental approach. (4th May 2020) - Klein, S.; Rose, T.
Abstract : Until today, raw material information of copper (Cu) objects is mostly gained from impurities and trace elements and not from the Cu itself. This might be obtained using its stable isotopes. However, isotopic fingerprinting requires the absence of fractionation during the smelting process. The Cu isotope evolution during outdoor smelting experiments with Cu sulphide ore was investigated. It is shown that external materials, in particular furnace lining, clay, manure and sand, alter the isotopic composition of the smelting products. Cu isotopes are fractionated within low viscosity slag derived from matte smelting. The produced metallic Cu has a Cu isotope signature close to the ore.